Changes in the plasma lipidome of healthy subjects after coffee consumption reveal potential cardiovascular benefits: A randomized controlled trial - Lara-Guzmán, Oscar J.; Álvarez, Rafael; Muñoz-Durango, Katalina (Free radical biology & medicine, 2021)
Lipid metabolism dysregulation is associated with cardiovascular disease (CVD) risk. Specific oxidized lipids are recognized CVD biomarkers involved in all stages of atherosclerosis, including foam cell formation. Moderate coffee intake is positively associated with cardiovascular health. A randomized, controlled (n = 25) clinical trial was conducted in healthy subjects to assess the changes in lipid species relevant to CVD (main inclusion criteria: coffee drinkers, nonsmokers, with no history and/or diagnosis of chronic disease and not consuming any medications). Volunteers consumed a coffee beverage (400 mL/day) containing either 787 mg (coffee A; n = 24) or 407 mg (coffee B; n = 25) of chlorogenic acids for eight weeks. We measured the total plasma levels of 46 lipids, including fatty acids, sterols, and oxysterols, at baseline and after eight weeks and assessed the effects of chlorogenic and phenolic acids, the major coffee antioxidants, in an in vitro foam cell model via targeted lipidomics. At baseline (n = 74), all participants presented oxysterols and free fatty acids (FFAs) (CVD risk markers), which are closely correlated to among them, but not with the classical clinical variables (lipid profile, waist circumference, and BMI). After eight weeks, the control group lipidome showed an increase in oxysterols (+7 ± 10%) and was strongly correlated with FFAs (e.g., arachidonic acid) and cholesteryl ester reduction (−13 ± 7%). Notably, the coffee group subjects (n = 49) had increased cholesteryl esters (+9 ± 11%), while oxysterols (−71 ± 30%) and FFAs (−29 ± 26%) decreased. No differences were found between the consumption of coffees A and B. Additionally, coffee antioxidants decreased oxysterols and regulated arachidonic acid in foam cells. Our results suggest that coffee consumption modulates the generation of oxidized and inflammatory lipids in healthy subjects, which are fundamental during CVD development. The clinical trial was registered on the International Clinical Trials Registry Platform, WHO primary registry (RPCEC00000168). [Display omitted] •Oxysterols are markers of oxidative stress that are associated with proinflammatory free fatty acids in healthy subjects.•Halting coffee consumption in coffee drinkers increased plasma levels of oxysterols and free fatty acids.•Moderate coffee consumption decreased plasma levels of oxysterols and free fatty acids.•Phenolic acids from coffee regulate oxysterol and fatty acid contents in foam cells.